Pedagogiczne i socjologiczne spojrzenie na zdrowie i bezpieczeństwo zdrowotne Polaków - Stefańska, Anita; Marcinkowski, Marian (Studia Edukacyjne, 2018)
The societies of developed countries, including Poland, are characterized by the dissemination of manifestations of the consumer lifestyle, which leads to a systematic deterioration of health and quality of life. The health and health safety should be systematically monitored and given in-depth scientific analyses, also from the perspective of pedagogy and sociology. In the scientific discourse there are various issues concerning both health hazards (inter alia related to globalization changes and lifestyle) and health promotion (for example, shaping pro-health attitudes and dissemination of participation in physical culture). Promoting a healthy lifestyle must be accompanied by investments in the material cultural-educational and sports-recreational base as well as by educational influences shaping the necessary level of knowledge and skills in the field of health.